Shariah, social, environmental & governance disclosure of Islamic banks in Malaysia - Andinarianti, Marrisa (2025)
This study examines Shariah, social, environmental, and governance (SSEG) disclosures in Malaysian Islamic banks from 2019 to 2023. Employing a qualitative exploratory approach with content analysis methodology, the research systematically evaluates annual reports from four institutions: Bank Islam Malaysia Berhad (BIMB), Bank Muamalat Malaysia Berhad (BMMB), Malaysia Building Society Berhad (MBSB), and Hong Leong Islamic Bank (HLISB). The primary objectives are to evaluate the corporate social responsibility (CSR) disclosure performance of these banks and to compare the differences in the use of phrases and graphical content in their disclosures. The findings indicate a significant trend towards enhanced transparency and a stronger commitment to social initiatives, particularly in the realms of Shariah compliance and governance. Moreover, the research contribute to the body of the literature by identifying critical gaps in environmental sustainability disclosures, suggesting that these banks have not adequately addressed their strategies and actions relating to environmental protection. This deficiency poses a challenge in aligning with global sustainability demands and highlights the need for improved accountability in environmental matters. Overall, the study underscores the evolving landscape of CSR practices among Islamic banks in Malaysia, reflecting both progress and areas requiring further development.